Reduced knee flexion is a possible cause of increased loading rates in individuals with patellofemoral pain - Silva, Danilo de Oliveira [UNESP]; Briani, Ronaldo Valdir [UNESP]; Pazzinatto, Marcella Ferraz [UNESP]; Ferrari, Deisi; Aragão, Fernando Amâncio; Azevedo, Fábio Mícolis de [UNESP] (Elsevier B. V., 2015)
Stair ascent is an activity that exacerbates symptoms of individuals with patellofemoral pain. The discomfort associated with this activity usually results in gait modification such as reduced knee flexion in an attempt to reduce pain. Although such compensatory strategy is a logical approach to decrease pain, it also reduces the normal active shock absorption increasing loading rates and may lead to deleterious and degenerative changes of the knee joint. Thus, the aims of this study were (i) to investigate whether there is reduced knee flexion in adults with PFP compared to healthy controls; and (ii) to analyze loading rates in these subjects, during stair climbing. Twenty-nine individuals with patellofemoral pain and twenty-five control individuals (18-30years) participated in this study. Each subject underwent three-dimensional kinematic and kinetic analyses during stair climbing on two separate days. Between-groups analyses of variance were performed to identify differences in peak knee flexion and loading rates. Intraclass correlation coefficient was performed to verify the reliability of the variables. On both days, the patellofemoral pain group demonstrated significantly reduced peak knee flexion and increased loading rates. In addition, the two variables obtained high to very high reliability. Reduced knee flexion during stair climbing as a strategy to avoid anterior knee pain does not seem to be healthy for lower limb mechanical distributions. Repeated loading at higher loading rates may be damaging to lower limb joints.
Keywords: Kinetics; Reproducibility of results; Anterior knee pain; Kinematics; Patellofemoral joint